Pengaruh dan Keterkaitan Kecemasan Matematika dan Self-efficacy Peserta Didik - Meilinda, Mutiara Dwi (Universitas Muria Kudus, 2022)
The pandemic that occurred affected many sectors, one of which was the education sector. With online learning, various kinds of problems arise. One of them is worrying about anxiety in learning mathematics for students. Their initial negative perception of mathematics causes math anxiety. This study aims to determine the influence and relationship between mathematics and self-efficacy in students. This study uses a survey method with a quantitative approach. The subjects in this study found 200 respondents who were students of SMPN 2 Serang Baru from class VII to class IX. The data collected will be tested for correlation using SPSS. The study's results based on the Pearson correlation test showed that the significance value was 0.274, which means that there is a correlation that is not too strong or can be said to be small. The variable speed of mathematics and self-efficacy has a weak relationship because the correlation coefficient value is only 0.078. That is, the level of anxiety in students does not affect and is not related to the level of self-efficacy of students and vice versa.